2015
DOI: 10.1186/s12887-015-0431-7
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic, environmental and caring risk factors for childhood drowning deaths in Bangladesh

Abstract: BackgroundDrowning contributes to incapacity and early death in many countries. In low- and middle-income countries, children are the most susceptible to fatalities. Over 50 % of the global drowning deaths occur among children aged under 15 years old with children aged between 1 and 4 years of age being most at risk. In Bangladesh, drowning rates are 10 to 20 times more than those in other developing countries. The object of this study is to determine the socio-demographic, environmental and caring hazard issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
23
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 16 publications
2
23
0
1
Order By: Relevance
“…This can increase the risk of exposure especially among children playing in water bodies. Previous studies have also reported over 90% of fatal drowning events occurred in daylight hours 17 25…”
Section: Discussionmentioning
confidence: 94%
“…This can increase the risk of exposure especially among children playing in water bodies. Previous studies have also reported over 90% of fatal drowning events occurred in daylight hours 17 25…”
Section: Discussionmentioning
confidence: 94%
“…As expected, male children were more likely to die from unintentional injuries than females [5,10,11]. Male children demonstrate higher risk-taking behavior while parents tend to supervise female children more closely [25,43].…”
Section: Discussionmentioning
confidence: 85%
“…[ 1 ] In addition, factors such as poor swimming skills, easy access to open water sources either because of occupation or due to proximity to house, frequent traveling on water in boats or ships poorly maintained or manned by un-experienced drivers, flood disasters, infants left unsupervised near water, tourists unaware of prevalent risks, and lack of barriers limiting exposure to water bodies are some of the known potential risk factors. [ 1 2 3 4 ]…”
mentioning
confidence: 99%
“…[ 2 5 ] Thus, prevention is extremely crucial, and interventions such as creating barriers to restrict access to open water sources; building safe places for under-five children away from water sources; and teaching basic swimming, water safety, and safe rescue-related skills in schools will have a sizeable impact on the overall burden of the problem. [ 2 3 4 ] Further, measures such as training observers regarding safe rescue and resuscitation, creating awareness about the condition and susceptibility among children, establishing and enforcing safe boating regulations, ensuring preparedness to adequately respond to flood disasters, encouraging intersectoral coordination, and promoting well-designed studies to ascertain the high risk factors and impact of corrective strategies will also eventually reduce the incidence of drowning and its associated consequences. [ 2 3 4 5 ]…”
mentioning
confidence: 99%
See 1 more Smart Citation